2019
DOI: 10.1590/0034-7167-2018-0484
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety incidents identified by the caregivers of hospitalized children

Abstract: Objective: to analyze patient safety incidents identified by caregivers of hospitalized children. Method: a qualitative, exploratory-descriptive study was carried out with 40 caregivers of children hospitalized in three hospital institutions in the city of Porto Alegre, Rio Grande do Sul State, Brazil, from April to December 2016. Semi-structured, recorded and transcribed interviews were carried out in their entirety, submitted to a thematic analysis using the NVivo 11.0 software. Results: reports related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
1
11
0
10
Order By: Relevance
“…Todos os incidentes críticos descritos demonstram a importância dos pais estarem inseridos no processo de cuidado, pois seu envolvimento pode trazer contribuições importantes para a segurança no cuidado com o bebê, e auxiliar na detecção e prevenção de eventos adversos ou quase falhas que não são percebidos ou notificados pela equipe assistencial 5,8,24 . Quando os pais estão inseridos nos cuidados, eles se sentem parte deste cuidado, e assim podem ser considerados pilares na segurança do paciente 9,25 .…”
Section: Discussionunclassified
“…Todos os incidentes críticos descritos demonstram a importância dos pais estarem inseridos no processo de cuidado, pois seu envolvimento pode trazer contribuições importantes para a segurança no cuidado com o bebê, e auxiliar na detecção e prevenção de eventos adversos ou quase falhas que não são percebidos ou notificados pela equipe assistencial 5,8,24 . Quando os pais estão inseridos nos cuidados, eles se sentem parte deste cuidado, e assim podem ser considerados pilares na segurança do paciente 9,25 .…”
Section: Discussionunclassified
“…In this study, "caregiver" was defined as the person who takes on the role of assisting the patient in a situation of total and/or partial dependency from performing daily activities in the hospital environment (5) . In general, the participation of caregivers in health institutions is a reality; these are co-participants in the health-disease continuum (6) .…”
Section: Study Population and Samplementioning
confidence: 99%
“…Noteworthy data related to this problem, a qualitative study conducted in Porto Alegre, state of Rio Grande do Sul (RS), Brazil, with 40 informal caregivers of children hospitalized in pediatric wards, reported deficit in the guidelines on HH and failures in the hospital environment, such as the absence of sinks in the wards, which favors non-adherence to hand hygiene care (5) . Another observational study implemented in Fortaleza, state of Ceará (CE), with 50 caregivers, also identified flaws in the hospital's organizational structure related to the participants' dissatisfaction with the lack of necessary resources for HH, such as paper towels near the sinks (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Nesta pesquisa ocorreu algumas complicações de saúde de crianças relacionadas a falta de orientação aos responsáveis sobre estas pautas supracitadas, o qual viabilizou determinados danos ao paciente, como quedas, remoção acidental de dispositivos (Hoffmann et al, 2019). Salienta-se também que foi evidenciado como empecilho da segurança do paciente a falta de articulação entre os membros da equipe de saúde e erros relacionados a medicação (Tolosa, Leguizamón, & Dávila, 2018).…”
Section: Categoria 3-a Necessidade De Hospitalização Da Criança Na Utipunclassified